Revisiting social support and academic adjustment among international students: A systematic review and meta-analysis - Sari, Citra Ayu Kumala; Yoenanto, Nono Hery; Paramita, Pramesti Pradna (Journal of International Students, 2026)
International students face substantial challenges in adapting to academic environments, with academic adjustment playing a critical role in their educational outcomes. Social support has been widely recognized as a potential facilitator of this process; however, empirical evidence regarding its effectiveness remains inconsistent. This meta-analysis synthesizes existing evidence on the relationship between social support and academic adjustment among international students, following the PRISMA (2020) guidelines. Thirteen peer-reviewed quantitative studies (N = 6,233) identified through systematic searches of Scopus, Web of Science, ScienceDirect, ERIC, and ProQuest were included. Using a random-effects model with the Hunter–Schmidt estimator, the pooled analysis revealed a significant positive association (r = 0.365, 95% CI [0.295, 0.435], p < .001). Nevertheless, substantial heterogeneity was observed (I² = 84.9%). Subgroup analyses and meta-regression indicated that gender, host country, and measurement instruments did not adequately explain this heterogeneity.